2016
DOI: 10.3390/rs8050416
|View full text |Cite
|
Sign up to set email alerts
|

Remote Estimation of Vegetation Fraction and Flower Fraction in Oilseed Rape with Unmanned Aerial Vehicle Data

Abstract: This study developed an approach for remote estimation of Vegetation Fraction (VF) and Flower Fraction (FF) in oilseed rape, which is a crop species with conspicuous flowers during reproduction. Canopy reflectance in green, red, red edge and NIR bands was obtained by a camera system mounted on an unmanned aerial vehicle (UAV) when oilseed rape was in the vegetative growth and flowering stage. The relationship of several widely-used Vegetation Indices (VI) vs. VF was tested and found to be different in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 56 publications
2
69
0
1
Order By: Relevance
“…Oilseed rape (Brassica napus L.) is a major cash crop, as well as one of the principal sources of edible oil, high energy, and protein meal plant species in countries with moderate climate (e.g., China, Europe, Canada, India, Australia, etc.) [1][2][3]. Accurate maps for oilseed rape (OR) distribution are essential to guide macro decision-making which maintains balance in agricultural supply and demand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oilseed rape (Brassica napus L.) is a major cash crop, as well as one of the principal sources of edible oil, high energy, and protein meal plant species in countries with moderate climate (e.g., China, Europe, Canada, India, Australia, etc.) [1][2][3]. Accurate maps for oilseed rape (OR) distribution are essential to guide macro decision-making which maintains balance in agricultural supply and demand.…”
Section: Introductionmentioning
confidence: 99%
“…However, the shortages of small spatial coverage, as well as expensive cost of hyperspectral images, limit its application on regional OR mapping.The second category mainly applies supervised classification methods on multispectral images during the flowering period to identify and extract OR at the local scale, since the flowering period is the best phenology stage of identifying OR from other crops [11]. As a member of the Brassicaceae family, OR appears as bright-yellow flowers lasting 30 days (approximately a quarter of its entire growing season) [3,12], which leads to a large difference on the reflectance at green, red, and near-infrared bands when compared with other crop species during the same period because of the radiation reflected by the flower petals [13][14][15]. She et al [11] introduced the effectiveness of identifying OR from other crops during its flowering phase and the difficulty in other growing stages.…”
mentioning
confidence: 99%
“…The use of UAVs in agriculture [36][37][38]56,57,62], horticulture [51], plant ecology [66,68,89], and forestry [59,61,62,65] is increasing worldwide. However, UAVs were not heretofore used to quantify the flower production of black locust.…”
Section: Discussionmentioning
confidence: 99%
“…The UAS platform provides alternatives to space-borne platforms since optical data can be observed in a clear-high spatial/temporal resolution for the region of interest [23]. This technique has been used in research on ecology [24], precision agriculture/forestry [25,26] and even analyses for estimating vegetation cover [27][28][29]. UAS was successful [27] in clearly estimating vegetation fractions and flower fractions in crop fields with the changing VIs, and work by Chen et al [28] showed that utilizing UAS-captured imagery may clearly detect grassy vegetation covers due to its high-resolution data.…”
Section: Figurementioning
confidence: 99%
“…This technique has been used in research on ecology [24], precision agriculture/forestry [25,26] and even analyses for estimating vegetation cover [27][28][29]. UAS was successful [27] in clearly estimating vegetation fractions and flower fractions in crop fields with the changing VIs, and work by Chen et al [28] showed that utilizing UAS-captured imagery may clearly detect grassy vegetation covers due to its high-resolution data. RiihimĂ€kia et al [29] showed that the UAV-derived information can be aided by satellite-observed information in FVC estimations.…”
Section: Figurementioning
confidence: 99%